Homozygous pArg610del Mutation Unusually Associated With Severe Delay of Growth in 2 Acid Sphingomyelinase Deficiency–affected Sibs. Issue 6 (August 2020) - Naifar, Manel; Kallel, Faten; HadjKacem, Faten; Boudabous, Hela; Kallel, Rim; Boudawara, Tahia; Messaoud, Olfa; Tbib, Neji; Charfi, Nadia; Abid, Mohamed; Froissart, Roseline; Messedi, Sondes Hdiji; et al.
Abstract : Background: Typically, patients with Acid Sphingomyelinase Deficiency (ASMD) because of p.Arg610del mutation, have mild phenotype with normal linear growth. Observation: We reported the case of 2 Tunisian brothers who have been referred for splenomegaly, polyadenopathies, pubertal, and growth delay. Molecular testing of SMPD1 gene revealed the presence of a homozygous p.Arg610del mutation. Lysosphingomyelin and its isoform-509 were both increased confirming ASMD for both cases. Growth hormone deficiency was highly suspected but growth hormone response after stimulating tests was acceptable for both patients. Conclusions: There is no correlation between phenotype-genotype in case of p.Arg610del mutation that could be associated to a severe delay of growth.